The Influence Of Promotions And Facilities On Guest Decisions To Visit The Grand Arkenso Park View Hotel Semarang - Deviana Wulandari; Wenefrida Ardhian Ayu Hardiani; Krisnawati Setyaningrum Nugraheni ; Mochamad Miswanto Gunawan (International Conference On Digital Advanced Tourism Management And Technology, 2023)
Currently, business competition in the hospitality sector is very tight. then hotel management must be competitive in competing, management must carry out attractive promotions, also provide good facilities, so that they can influence consumer visits..The purpose of this research is to examine and analyze the influence of promotions and facilities on consumer visits. This research was conducted at the Grand Arkenso Park View Hotel Semarang. The sampling technique used the probability sampling technique with the accidental sampling method, and the data collection technique used the survey method through a questionnaire. The sample size taken using the Slovin formula is 92 respondents. data processing method using multiple linear regression method with the help of SPSS (Product Solutions and Service Statistics). The test results prove that promotions and facilities have a significant and positive effect visiting guest.